2020
DOI: 10.1002/brb3.1985
|View full text |Cite
|
Sign up to set email alerts
|

Early neurological deterioration in cardiogenic cerebral embolism due to nonvalvular atrial fibrillation: Predisposing factors and clinical implications

Abstract: Purpose The aim of the study was to investigate factors which may predispose patients to early neurological deterioration (END) and explore peripheral biomarkers for the prediction of END in cardiogenic cerebral embolism (CCE) patients. Methods Patients diagnosed with CCE within 24 hr of onset between January 2017 and January 2019 were included in this study. END was defined as an increase of ≥2 on the National Institutes of Health Stroke Scale (NIHSS) or the emergence of new neurological symptoms within 3 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 50 publications
(48 reference statements)
1
15
0
Order By: Relevance
“…After screening of the remaining 17 studies in full text, three studies without any data on NLR and END, two studies with missing SD data, one study including stroke patients suffering from cancer, one study without a control group, and one review article were excluded. Finally, nine articles were included in our study [15][16][17][18][19][20][21][22][23] (Figure 1).…”
Section: Eligible Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…After screening of the remaining 17 studies in full text, three studies without any data on NLR and END, two studies with missing SD data, one study including stroke patients suffering from cancer, one study without a control group, and one review article were excluded. Finally, nine articles were included in our study [15][16][17][18][19][20][21][22][23] (Figure 1).…”
Section: Eligible Studiesmentioning
confidence: 99%
“…By extension, NLR may be a predictor of END in stroke patients. Several studies have found that an elevated NLR is related to the development of END [15][16][17][18][19][20][21][22][23]. In light of the growing emphasis on classifying stroke patients for different levels of monitoring intensity and emergency treatments, we conducted a systematic review of a wide range of clinical studies, with no restrictions on the language or publication date, to analyze the potential of NLR as an END risk predictor.…”
Section: Introductionmentioning
confidence: 99%
“…Another recent research from China furtherly confirmed the essential role of Cystatin C in the END. Patients with cardiogenic cerebral embolism were enrolled in the study, and the results demonstrated Cystatin C was associated with END within 3 days of cardiogenic cerebral embolism ( Cong and Ma, 2021 ). However, this study had several limitations that excluded other types of cerebral infarction and not investigated the potential mechanism deeply.…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of END varies in different trials, ranging between 13% and one-third of patients [195][196][197][198] but has been reported by some researchers to be as high as 43% [199].…”
Section: Epidemiology Of Early Neurologic Deterioration (End)mentioning
confidence: 99%
“…• Hyperglycemia [198][199][200], which leads to increased concentrations of lactate and acidosis in the penumbral area [201], worsens mitochondrial function in the penumbra [202] and predicts poor outcome [203].…”
Section: Epidemiology Of Early Neurologic Deterioration (End)mentioning
confidence: 99%